A material preparation process with both concrete structure demoulding and anti-sticking and surface strengthening functions
Through the specific material combination in the preparation process, the problems of difficult demolding and poor surface quality of concrete structures are solved, efficient demolding and performance improvement are achieved, and the dimensional accuracy and performance stability of concrete structures are ensured.
Patent Information
- Application Number
- CN202411003753.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-25
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-07-25
AI Technical Summary
In civil engineering construction, the bonding effect between the concrete structure and the mold leads to difficulties in demolding, resulting in economic losses and environmental pollution, and affects the dimensional accuracy and performance of the concrete structure.
Using a material preparation process that combines mold release and anti-adhesion and surface strengthening functions, it uses fluorocarbon surfactant, isomer decaol polyoxyethylene ether, dimethyl silicone oil, sodium stearate, nanoγ-C2S, oxidation Materials such as graphene and glycerol form release base materials and surface reinforcement materials, reducing the adhesion between concrete and mold, and improving the waterproof and permeability of the concrete surface.
It realizes easy demolding of concrete structures, improves surface quality and performance, avoids the deterioration of concrete performance by traditional oil release agents, improves mold release efficiency and mold service life, and enhances the waterproof and seepage resistance of concrete.
Smart Images

Figure CN118813327B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of concrete materials, and in particular to a process for preparing a material having both concrete structure demoulding and anti-sticking functions and surface strengthening functions. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] A large number of concrete structures are used in the process of civil engineering construction. For example, precast concrete parts have been widely used in the fields of prefabricated buildings, bridge engineering, tunnel engineering, water conservancy and hydropower engineering, etc. Concrete structure precast parts are usually poured into molds in factories, and then demolded and cured to a predetermined age after hardening and forming. In the above demolding process, demolding is difficult due to the bonding effect between the concrete structure and the mold. After demolding, there are often residual accumulated and solidified cement-based materials on the surface of the mold, which need to be removed manually or washed with a large amount of water, causing economic losses and environmental pollution. In addition, the mold is easily deformed during the cleaning process, which not only affects the dimensional accuracy of the concrete structure, but also causes the mold to be unable to continue to be used after deformation accumulation caused by multiple cleanings.
[0004] At present, in order to facilitate demoulding, waste oil, paraffin and other substances are usually applied on the surface of the mold. However, these substances not only easily cause pollution to the construction environment and the mold and are difficult to clean, but also have poor demoulding effects. After demoulding, there is a significant color difference on the surface of the concrete structure. In addition, the concrete structure after demoulding often has poor surface quality, which leads to a decrease in the performance of the concrete structure and affects the service safety of the concrete structure. Summary of the invention
[0005] The present invention provides a material preparation process with both concrete structure demoulding and anti-sticking and surface strengthening functions, which not only has good demoulding performance, but also can improve the surface quality of the concrete structure, avoiding the problem that traditional oil-based demoulding agents easily deteriorate the performance of the concrete structure. Specifically, the technical solution of the present invention is as follows.
[0006] A material preparation process having both concrete structure demoulding and anti-sticking and surface strengthening functions, comprising the following steps:
[0007] (1) Mix the fluorocarbon surfactant and isomeric decanol polyoxyethylene ether, then add dimethyl silicone oil, mix well, add hot water, and mix well to obtain a reaction solution a.
[0008] (2) The reaction solution a is mixed with the sodium stearate solution, and then isopropyl alcohol is added, mixed, and then diluted with water to obtain a demoulding base material for later use.
[0009] (3) Add polycarboxylic acid water reducer to the aqueous dispersion of nano-γ-C2S and mix well. After completion, separate the solid product and freeze-dry it to obtain modified nano-γ-C2S.
[0010] (4) Adding a polycarboxylic acid water reducer to the aqueous dispersion of graphene oxide and mixing well, separating the solid product and freeze-drying it to obtain modified graphene oxide.
[0011] (5) The modified nano-γ-C2S, modified graphene oxide, sodium stearate and glycerol diluent are mixed to obtain a surface strengthening material for later use.
[0012] (6) The demoulding base material and the surface strengthening material are stored separately. When in use, the demoulding base material is first applied to the inner surface of the concrete casting mold, and after drying and solidifying to form a film, the sodium alginate solution is applied, and then the surface strengthening material is sprayed, so that the concrete structure demoulding and surface strengthening functional materials are formed, and then the concrete is poured.
[0013] Furthermore, in step (1), the mass ratio of the fluorocarbon surfactant, isomeric decanol polyoxyethylene ether, and dimethyl silicone oil is 2-6:1-3:2-5.
[0014] Furthermore, in step (1), the mass ratio of the hot water to the dimethyl silicone oil is 250-300:2-5. Optionally, the temperature of the hot water is 55-70°C.
[0015] Furthermore, in step (2), the mass ratio of the reaction solution a to the sodium stearate solution is 1:1.3-1.5. Optionally, the mass fraction of the sodium stearate solution is 1-3%.
[0016] Furthermore, in step (2), the molar ratio of the reaction solution a to isopropanol is 1:0.025-0.06.
[0017] Furthermore, in step (2), the dilution multiple of adding water is 4 to 5 times.
[0018] Furthermore, in step (3), the mass ratio of the nano-γ-C2S to the polycarboxylate water-reducing agent is 1:0.025-0.04. Optionally, the solid content of the aqueous dispersion of the nano-γ-C2S is 20-40 g / L.
[0019] Furthermore, in step (4), the mass ratio of the graphene oxide to the polycarboxylate water reducer is 1:0.015-0.022. Optionally, the solid content of the aqueous dispersion of the graphene oxide is 5-10 g / L.
[0020] Furthermore, in step (5), the ratio of the modified nano-γ-C2S, modified graphene oxide, sodium stearate, and glycerol diluent is 3-5 g: 1-1.5 g: 10-17 g: 500 ml. Optionally, the glycerol diluent is formed by mixing glycerol and water in a volume ratio of 1:1-2.
[0021] Furthermore, in step (5), the mass fraction of the sodium alginate solution is 0.5-1%.
[0022] Furthermore, in step (6), the coating thickness of the demoulding base material is 0.2-0.5 mm. Optionally, the curing time is 20-24 hours.
[0023] Furthermore, in step (6), the coating thickness of the sodium alginate solution is 0.1-0.2 mm.
[0024] Furthermore, in step (6), the coating thickness of the surface strengthening material is 0.2-0.5 mm.
[0025] Compared with the prior art, the present invention has at least the following beneficial technical effects:
[0026] The material of the present invention not only makes it easy for the concrete structure to be demoulded from the mold, but also can improve the surface quality of the concrete structure and improve the performance of the concrete structure. First, the present invention uses the demoulding base material to be coated on the mold surface and solidified to form an anti-sticking coating, which can effectively reduce the interlocking force between the concrete structure and the mold surface. Among them, the two lubricating materials of isopropyl alcohol and fluorocarbon surfactant provide excellent lubrication performance for the anti-sticking coating, which can reduce the friction between the contact surfaces. At the same time, the fluorocarbon surfactant and dimethyl silicone oil make the anti-sticking coating have a lower surface energy, which can effectively reduce the adhesion between the concrete structure and the mold. The sodium stearate, dimethyl silicone oil and fluorocarbon surfactant also make the surface of the anti-sticking coating have good hydrophobicity, increase the contact angle with the mold surface, and then reduce the water film viscosity resistance and water ring viscosity resistance, so that the concrete structure is not easy to bond with the mold surface. Then, the present invention also first coats a layer of sodium alginate solution on the anti-sticking coating and then sprays the surface strengthening material, which can not only further improve the demoulding between the concrete structure and the mold, but also strengthen the concrete surface. For this reason, the present invention first uses polycarboxylate water reducer to process nano γ-C2S and graphene oxide, utilizes the electrostatic action of carboxyl on water reducer to adsorb on nano γ-C2S and graphene oxide, reduces the action force between nano γ-C2S particles and between graphene oxide particles, and is convenient for the dispersion of nano γ-C2S and graphene oxide. Then it is formed into surface strengthening material with sodium stearate and glycerol diluent, and is sprayed on the sodium alginate solution layer when used. After concrete material is poured into the mold with the above-mentioned material layer, the nano γ-C2S and graphene oxide penetrate into the concrete surface layer, and the polycarboxylate water reducer loaded on the nano γ-C2S and graphene oxide helps to reduce the capture of nano γ-C2S and graphene oxide by cement material, improves its permeability, and improves the waterproof and impermeability of concrete structure. After the sodium stearate enters the surface layer of the concrete material, it reacts with calcium ions under the alkaline conditions generated by cement hydration to form solid calcium stearate particles, which can not only improve the surface compactness of the concrete structure, but also improve the waterproof and impermeability of the concrete structure due to its good hydrophobicity. At the same time, the nano γ-C2S also overcomes the problem that the formation of calcium stearate causes the hydration product calcium hydroxide to be consumed, resulting in a decrease in the alkalinity of the surface layer of the concrete structure and a decrease in the carbonation resistance. The glycerol can quickly dissolve into the mixing water in the concrete material after encountering it. On the one hand, the glycerol can reduce the rate of condensation of the surface layer of the concrete material, which is convenient for the penetration of the nano γ-C2S and graphene oxide. On the other hand, the traction effect formed by the rapid dissolution and diffusion of glycerol into the concrete material also helps to promote the penetration of nano γ-C2S and graphene oxide.On the other hand, the surface strengthening material also has the function of inhibiting the calcium ions provided by the sodium alginate solution in the initial hydration reaction with the concrete to form a cross-linked film, so that after the surface strengthening material fully penetrates into the concrete material, the sodium alginate is cross-linked to form a film, thereby forming an isolation layer between the concrete material and the demoulding base material layer. Since the isolation layer and the demoulding base material layer are very easy to desorb, the demoulding property is further improved, and the service life of the anti-sticking coating formed by the demoulding base material is improved. At the same time, the sodium alginate that enters the concrete material can also improve the waterproof and impermeability after cross-linking and forming a film. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0028] Figure 1 This is a sample photo of the release substrate material prepared in Example 1 below. DETAILED DESCRIPTION
[0029] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.
[0030] Unless otherwise defined, all professional and scientific terms used in the present invention have the same meanings as those familiar to those skilled in the art. The reagents or raw materials used in the present invention can be purchased through conventional channels. If there are no special instructions, the reagents or raw materials used in the present invention are used in a conventional manner in the art or in accordance with the product instructions. In addition, any method and material similar to or equivalent to the described content can be applied to the method of the present invention. Now, the technical solution of the present invention is further described in conjunction with the accompanying drawings and specific embodiments of the specification.
[0031] Example 1
[0032] A material preparation process having both concrete structure demoulding and anti-sticking and surface strengthening functions, comprising the following steps:
[0033] (1) A fluorocarbon surfactant and isomeric decanol polyoxyethylene ether were mixed and stirred for 1 min, and then dimethyl silicone oil was added. After mixing, hot water at 60° C. was added and mixed to obtain a reaction solution a. The fluorocarbon surfactant (FSN-100, Guangzhou Jie Lu Hua Biotechnology Co., Ltd.), isomeric decanol polyoxyethylene ether, dimethyl silicone oil, and hot water were added in a mass ratio of 3:2:3:280.
[0034] (2) Mix the reaction solution a with a 2% sodium stearate solution by mass and stir evenly, then add isopropyl alcohol and mix evenly, then dilute with water by 5 times to obtain a demoulding base material for later use. The reaction solution a, sodium stearate solution and isopropyl alcohol are added in a mass ratio of 1:1.4:0.05.
[0035] (3) Add polycarboxylate water reducer to the aqueous dispersion of nano-γ-C2S with a solid content of 30 g / L and stir evenly, and the mass ratio of the nano-γ-C2S to the polycarboxylate water reducer is 1:0.03. After completion, the solid product is separated by centrifugation and freeze-dried to obtain modified nano-γ-C2S.
[0036] (4) Adding a polycarboxylic acid water reducer to a water dispersion of graphene oxide having a solid content of 10 g / L and stirring the mixture evenly, wherein the mass ratio of the graphene oxide to the polycarboxylic acid water reducer is 1:0.02. After completion, separating the solid product and freeze-drying it, the modified graphene oxide is obtained.
[0037] (5) The modified nano-γ-C2S, modified graphene oxide, sodium stearate and glycerol diluent (glycerol and water are mixed in a volume ratio of 1:1.5) are mixed in a ratio of 4g:1.2g:15g:500ml and then ultrasonically dispersed for 2 minutes to obtain a surface strengthening material for later use.
[0038] (6) When in use, first place the demoulding base material (such as Figure 1 As shown in the figure, the inner surface of the concrete casting mold is brushed (the coating thickness is 0.5 mm), and then dried and cured at room temperature for 24 hours to form a film. Then, a sodium alginate solution with a mass fraction of 1% is brushed (the coating thickness is 0.1 mm). After completion, the surface strengthening material prepared in this embodiment is brushed (the coating thickness is 0.5 mm), that is, a concrete structure demoulding and surface strengthening functional material is formed, and then concrete is poured, demoulding is performed after hardening, and natural curing is performed for 7 days to obtain a concrete specimen.
[0039] The demoulding performance (JC / T949-2020) of the concrete structure demoulding and surface strengthening functional material prepared in this embodiment and the anti-permeability performance (GB / T 50082-2009) and anti-carbonization performance (GB / T 50082-2009) of the concrete specimens were tested. The results are shown in Table 1 below:
[0040] Table 1
[0041] .
[0042] Example 2
[0043] A material preparation process having both concrete structure demoulding and anti-sticking and surface strengthening functions, comprising the following steps:
[0044] (1) A fluorocarbon surfactant and isomeric decanol polyoxyethylene ether were mixed and stirred for 1 min, and then dimethyl silicone oil was added. After mixing, hot water at 70° C. was added and mixed to obtain a reaction solution a. The fluorocarbon surfactant (FSN-100, Guangzhou Jie Lu Hua Biotechnology Co., Ltd.), isomeric decanol polyoxyethylene ether, dimethyl silicone oil, and hot water were added in a mass ratio of 2:1:2:250.
[0045] (2) Mix the reaction solution a with a 3% sodium stearate solution by mass and stir evenly, then add isopropyl alcohol and mix evenly, then dilute with water by 4 times to obtain a demoulding base material for later use. The reaction solution a, sodium stearate solution and isopropyl alcohol are added in a mass ratio of 1:1.3:0.025.
[0046] (3) Adding polycarboxylate water reducer to the aqueous dispersion of nano-γ-C2S with a solid content of 40 g / L and stirring evenly, the mass ratio of the nano-γ-C2S to the polycarboxylate water reducer is 1:0.04. After completion, the solid product is separated by centrifugation and freeze-dried to obtain modified nano-γ-C2S.
[0047] (4) Adding a polycarboxylic acid water reducer to a water dispersion of graphene oxide having a solid content of 5 g / L and stirring the mixture evenly, wherein the mass ratio of the graphene oxide to the polycarboxylic acid water reducer is 1:0.015. After completion, separating the solid product and freeze-drying it to obtain modified graphene oxide.
[0048] (5) The modified nano-γ-C2S, modified graphene oxide, sodium stearate and glycerol diluent (glycerol and water are mixed in a volume ratio of 1:1) are mixed in a ratio of 3g:1g:10g:500ml and then ultrasonically dispersed for 2 minutes to obtain a surface strengthening material for later use.
[0049] (6) When in use, first apply the demoulding base material prepared in this embodiment to the inner surface of the concrete casting mold (the coating thickness is 0.3 mm), and then dry and solidify at room temperature for 20 hours to form a film. Then apply a sodium alginate solution with a mass fraction of 0.5% (the coating thickness is 0.2 mm). After completion, apply the surface strengthening material prepared in this embodiment (the coating thickness is 0.3 mm) to form a concrete structure demoulding and surface strengthening functional material, and then cast the concrete, demould after hardening, and naturally cure for 7 days to obtain a concrete specimen.
[0050] The demoulding performance of the concrete structure demoulding and surface strengthening functional material prepared in this embodiment and the anti-permeability and anti-carbonization performance of the concrete specimens were tested by the same method as in Example 1. The results are shown in Table 2 below:
[0051] Table 2
[0052] .
[0053] Example 3
[0054] A material preparation process having both concrete structure demoulding and anti-sticking and surface strengthening functions, comprising the following steps:
[0055] (1) A fluorocarbon surfactant and isomeric decanol polyoxyethylene ether were mixed and stirred for 1 min, and then dimethyl silicone oil was added. After mixing, hot water at 55° C. was added and mixed to obtain a reaction solution a. The fluorocarbon surfactant (FSN-100, Guangzhou Jie Lu Hua Biotechnology Co., Ltd.), isomeric decanol polyoxyethylene ether, dimethyl silicone oil, and hot water were added in a mass ratio of 6:3:5:300.
[0056] (2) Mix the reaction solution a with a sodium stearate solution having a mass fraction of 1% and stir evenly, then add isopropyl alcohol and mix evenly, then dilute with water by 4 times to obtain a demoulding base material for later use. The reaction solution a, sodium stearate solution and isopropyl alcohol are added in a mass ratio of 1:1.5:0.06.
[0057] (3) Adding polycarboxylate water reducer to the aqueous dispersion of nano-γ-C2S with a solid content of 20 g / L and stirring evenly, the mass ratio of the nano-γ-C2S to the polycarboxylate water reducer is 1:0.025. After completion, the solid product is separated by centrifugation and freeze-dried to obtain modified nano-γ-C2S.
[0058] (4) Adding a polycarboxylic acid water reducer to a water dispersion of graphene oxide having a solid content of 8 g / L and stirring the mixture evenly, wherein the mass ratio of the graphene oxide to the polycarboxylic acid water reducer is 1:0.022. After completion, separating the solid product and freeze-drying it, the modified graphene oxide is obtained.
[0059] (5) The modified nano-γ-C2S, modified graphene oxide, sodium stearate and glycerol diluent (glycerol and water are mixed in a volume ratio of 1:2) are mixed in a ratio of 5g:1.5g:17g:500ml and then ultrasonically dispersed for 3 minutes to obtain a surface strengthening material for later use.
[0060] (6) When in use, first apply the demoulding base material prepared in this embodiment to the inner surface of the concrete casting mold (the coating thickness is 0.2 mm), and then dry and solidify at room temperature for 20 hours to form a film. Then apply a sodium alginate solution with a mass fraction of 1% (the coating thickness is 0.1 mm). After completion, apply the surface strengthening material prepared in this embodiment (the coating thickness is 0.2 mm) to form a concrete structure demoulding and surface strengthening functional material, and then cast the concrete, demould after hardening, and naturally cure for 7 days to obtain a concrete specimen.
[0061] The demoulding performance of the concrete structure demoulding and surface strengthening functional material prepared in this embodiment and the anti-permeability and anti-carbonization performance of the concrete specimens were tested by the same method as in Example 1. The results are shown in Table 3 below:
[0062] Table 3
[0063] .
[0064] Example 4
[0065] A material preparation process having both concrete structure demoulding and anti-sticking and surface strengthening functions, comprising the following steps:
[0066] (1) Mix nano-γ-C2S, graphene oxide, sodium stearate and glycerol diluent (glycerol and water are mixed in a volume ratio of 1:1.5) in a ratio of 4g:1.2g:15g:500ml, and then ultrasonically disperse for 2 minutes to obtain a surface strengthening material for later use.
[0067] (2) When in use, first apply the demoulding base material prepared in Example 1 to the inner surface of the concrete casting mold (the coating thickness is 0.5 mm), and then dry and solidify at room temperature for 24 hours to form a film. Then apply a sodium alginate solution with a mass fraction of 1% (the coating thickness is 0.1 mm). After completion, apply the surface strengthening material prepared in this example (the coating thickness is 0.5 mm) to form a concrete structure demoulding and surface strengthening functional material, and then cast the concrete, demould after hardening, and naturally cure for 7 days to obtain a concrete specimen.
[0068] The demoulding performance of the concrete structure demoulding and surface strengthening functional material prepared in this embodiment and the anti-permeability and anti-carbonization performance of the concrete specimens were tested by the same method as in Example 1. The results are shown in Table 4 below:
[0069] Table 4
[0070] .
[0071] Example 5
[0072] A material preparation process having both concrete structure demoulding and anti-sticking and surface strengthening functions, comprising the following steps:
[0073] First, a sodium alginate solution with a mass fraction of 1% was brushed on the inner surface of the concrete casting mold (the coating thickness was 0.1 mm), and then the surface strengthening material prepared in Example 3 was brushed (the coating thickness was 0.2 mm), that is, the concrete structure demoulding and surface strengthening functional material was formed, and then the concrete was poured, demoulded after hardening, and naturally cured for 7 days to obtain a concrete specimen.
[0074] The demoulding performance of the concrete structure demoulding and surface strengthening functional material prepared in this embodiment and the anti-permeability and anti-carbonization performance of the concrete specimens were tested by the same method as in Example 1. The results are shown in Table 5 below:
[0075] Table 5
[0076] .
[0077] Example 6
[0078] A material preparation process having both concrete structure demoulding and anti-sticking and surface strengthening functions, comprising the following steps:
[0079] First, the demoulding base material prepared in Example 1 was applied on the inner surface of the concrete casting mold (the coating thickness was 0.5 mm), and then dried and cured at room temperature for 24 hours to form a film. Then, the surface strengthening material prepared in Example 1 was applied (the coating thickness was 0.5 mm) to form a concrete structure demoulding and surface strengthening functional material, and then the concrete was poured, demoulded after hardening, and naturally cured for 7 days to obtain a concrete specimen.
[0080] The demoulding performance of the concrete structure demoulding and surface strengthening functional material prepared in this embodiment and the anti-permeability and anti-carbonization performance of the concrete specimens were tested using the same method as in Example 1. The results are shown in the following table:
[0081] Table 6
[0082] .
[0083] Example 7
[0084] A material preparation process having both concrete structure demoulding and anti-sticking and surface strengthening functions, comprising the following steps:
[0085] (1) The modified graphene oxide prepared in Example 3, sodium stearate and glycerol diluent (glycerol and water are mixed in a volume ratio of 1:2) are mixed in a ratio of 1.5 g:17 g:500 ml and then ultrasonically dispersed for 3 minutes to obtain a surface strengthening material for later use.
[0086] (2) When in use, first apply the demoulding base material prepared in Example 3 to the inner surface of the concrete casting mold (the coating thickness is 0.2 mm), and then dry and solidify at room temperature for 20 hours to form a film. Then apply a sodium alginate solution with a mass fraction of 1% (the coating thickness is 0.1 mm). After completion, apply the surface strengthening material prepared in this example (the coating thickness is 0.2 mm) to form a concrete structure demoulding and surface strengthening functional material, and then cast the concrete, demould after hardening, and naturally cure for 7 days to obtain a concrete specimen.
[0087] The demoulding performance of the concrete structure demoulding and surface strengthening functional material prepared in this embodiment and the anti-permeability and anti-carbonization performance of the concrete specimens were tested using the same method as in Example 1. The results are shown in the following table:
[0088] Table 7
[0089] .
[0090] Example 8
[0091] A material preparation process having both concrete structure demoulding and anti-sticking and surface strengthening functions, comprising the following steps:
[0092] (1) The modified nano-γ-C2S of Example 2, the modified graphene oxide of Example 2, sodium stearate and anhydrous ethanol were mixed in a ratio of 3 g: 1 g: 10 g: 500 ml and then ultrasonically dispersed for 2 min to obtain a surface strengthening material for later use.
[0093] (2) When in use, first apply the demoulding base material of Example 2 to the inner surface of the concrete casting mold (the coating thickness is 0.3 mm), and then dry and solidify at room temperature for 20 hours to form a film. Then apply a sodium alginate solution with a mass fraction of 0.5% (the coating thickness is 0.2 mm). After completion, apply the surface strengthening material prepared in this example (the coating thickness is 0.3 mm) to form a concrete structure demoulding and surface strengthening functional material, and then cast the concrete, demould after hardening, and naturally cure for 7 days to obtain a concrete specimen.
[0094] The demoulding performance of the concrete structure demoulding and surface strengthening functional material prepared in this embodiment and the anti-permeability and anti-carbonization performance of the concrete specimens were tested using the same method as in Example 1. The results are shown in the following table:
[0095] Table 8
[0096] .
[0097] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A material preparation process with both concrete structure demoulding and anti-sticking and surface strengthening functions, characterized in that: The steps include: (1) Mix the fluorocarbon surfactant and isomeric decanol polyoxyethylene ether, then add dimethyl silicone oil, mix well, add hot water, and mix well to obtain a reaction solution a; (2) Mix the reaction solution a and the sodium stearate solution, then add isopropyl alcohol, mix well, and dilute with water to obtain a demoulding base material for later use; (3) adding polycarboxylic acid water reducer to the aqueous dispersion of nano-γ-C2S and mixing well, separating the solid product and freeze-drying it to obtain modified nano-γ-C2S; (4) adding a polycarboxylic acid water reducer to the aqueous dispersion of graphene oxide and mixing well, separating the solid product and freeze-drying it to obtain modified graphene oxide; (5) Mixing the modified nano-γ-C2S, modified graphene oxide, sodium stearate and glycerol diluent to obtain a surface strengthening material for later use; (6) The demoulding base material and the surface strengthening material are stored separately; when in use, the demoulding base material is first applied to the inner surface of the concrete casting mold, and after drying and solidifying to form a film, the sodium alginate solution is applied, and then the surface strengthening material is sprayed to form a concrete structure demoulding and surface strengthening functional material; wherein: the mass fraction of the sodium alginate solution is 0.5-1%; the coating thickness of the demoulding base material is 0.3-0.5 mm; the curing time is 20-24 hours; the coating thickness of the sodium alginate solution is 0.1-0.2 mm; the coating thickness of the surface strengthening material is 0.3-0.5 mm.
2. The process for preparing a material having both the functions of concrete structure demoulding and anti-sticking and surface strengthening according to claim 1, characterized in that: In step (1), the mass ratio of the fluorocarbon surfactant, isomeric decanol polyoxyethylene ether, and dimethyl silicone oil is 2-6:1-3:2-5.
3. The process for preparing a material having both the functions of concrete structure demoulding and anti-sticking and surface strengthening according to claim 1, characterized in that: In step (1), the mass ratio of hot water to dimethyl silicone oil is 250-300:2-5.
4. The process for preparing a material having both the functions of concrete structure demoulding and anti-sticking and surface strengthening according to claim 3, characterized in that: In step (1), the temperature of the hot water is 55-70°C.
5. The process for preparing a material having both the functions of concrete structure demoulding and anti-sticking and surface strengthening according to claim 1, characterized in that: In step (2), the mass ratio of the reaction solution a to the sodium stearate solution is 1:1.3-1.
5.
6. The process for preparing a material having both the functions of concrete structure demoulding and anti-sticking and surface strengthening according to claim 5, characterized in that: The mass fraction of the sodium stearate solution is 1-3%.
7. The process for preparing a material having both the functions of concrete structure demoulding and anti-sticking and surface strengthening according to claim 1, characterized in that: In step (2), the mass ratio of the reaction solution a to isopropanol is 1:0.025-0.
06.
8. The process for preparing a material having both the functions of concrete structure demoulding and anti-sticking and surface strengthening according to claim 1, characterized in that: In step (2), the dilution multiple of adding water is 4 to 5 times.
9. The process for preparing a material having both the functions of concrete structure demoulding and anti-sticking and surface strengthening according to claim 1, characterized in that: In step (3), the mass ratio of the nano-γ-C2S to the polycarboxylate water-reducing agent is 1:0.02-0.
04.
10. The process for preparing a material having both the functions of concrete structure demoulding and anti-sticking and surface strengthening according to claim 1, characterized in that: In step (3), the solid content of the aqueous dispersion of nano-γ-C2S is 20-40 g / L.
11. The process for preparing a material having both the functions of concrete structure demoulding and anti-sticking and surface strengthening according to claim 1, characterized in that: In step (4), the mass ratio of graphene oxide to polycarboxylic acid water reducer is 1:0.015-0.
022.
12. The process for preparing a material having both the functions of concrete structure demoulding and anti-sticking and surface strengthening according to claim 1, characterized in that: In step (4), the solid content of the aqueous dispersion of graphene oxide is 5-10 g / L.
13. The process for preparing a material having both the functions of concrete structure demoulding and anti-sticking and surface strengthening according to any one of claims 1 to 12, characterized in that: In step (5), the ratio of the modified nano-γ-C2S, modified graphene oxide, sodium stearate, and glycerol diluent is 3g~5g: 1g~1.5g: 10g~17g: 500ml.
14. The process for preparing a material having both the functions of concrete structure demoulding and anti-sticking and surface strengthening according to claim 13, characterized in that: The glycerol diluent is formed by mixing glycerol and water in a volume ratio of 1:1-2.
